Exploring social media fatigue among youth in the United Arab Emirates - S. Y. Al-Jallad, Marian; Farouk Radwan, Ahmed (Journal of Print and Media Technology Research, 2021)
Social media fatigue (SMF) has emerged as a recent phenomenon by which social media users feel fatigued and exhausted as a result of the great amount of technological and psychosocial pressures they are exposed to online, consequently, affecting their psychological well-being. Therefore, this study explores the antecedents and consequences of SMF among young adults in the United Arab Emirates through a cross-sectional study with 350 users. From the lens of the stressor–strain–outcome framework, cognitive load theory, and selective exposure and selective avoidance theory, our study explores the relationship between the antecedents: three technological factors (information overload, system-feature overload, and privacy concerns), three psychosocial factors (fear of missing out, self-disclosure, and social comparison) and SMF. Additionally, the study explores the behavioral consequences resulting from SMF such as discontinued use, switching intention, and the proper coping mechanisms that social media users utilize when experiencing SMF. The empirical results show that the technological and psychosocial antecedents are significantly positively correlated with SMF. Furthermore, users who experience SMF engage in different usage behaviors including discontinued use, willingness to switch, and utilize coping mechanisms when they are exposed to SMF.